Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Model Problem Based Learning Berbantuan Power Point pada Fase E SMA Negeri 1 Lumar - Lidya Verawaty; Y L Sukestiyarno; Martina Murlani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The main goal of education at school is the students’ achievement. Therefore, teachers must be knowledgeable about various teaching methods and implement them during their lessons. In order for students to achieve the intended learning outcomes, teachers must employ appropriate teaching methods during classroom activities. The purpose of this research is to identify student independence in learning through the use of a Problem-Based Learning model supported by PowerPoint in Phase E, involving 19 students from SMA Negeri 1 Lumar. This research was conducted over two cycles with the topic ‘Aku Pribadi yang Unik’. 1) The PBL model is effective in improving students’ dimensions of learning independence, as evidenced by a 12% increase. 2) There is also potential for improvement in students’ cognitive learning outcomes. 3) Furthermore, this model can enhance the achievement of psychomotor learning outcomes.